Inactivation of Escherichia coli O157: H7 by treatment with different temperatures of micro-bubbles ozone containing water - Chuajedton A. (2017)
© All Rights Reserved. This study investigated the effect of micro-bubbles ozone containing water at 13°C and 28°C on inactivation of Escherichia coli O157:H7. Oxidation reduction potential (ORP) and pH were measured for oxidation reaction of micro-bubbles ozone which resulting in an increase of ORP and decrease of pH with reaction times. The cell suspension of E. coli O157:H7 exposed to micro-bubbles ozone concentration of 0.01, 0.03, 0.05, and 0.02 mg O 3 /L at 28°C and the concentration of 0.14, 0.17, 0.14, and 0.18 mg O 3 /L at 13°C for 5, 10, 15 and 30 min, respectively and subsequently incubated at 35°C for 48 hr. The results showed that microbubbles ozone exhibited the most effectiveness to inactivate the growth of E. coli O157:H7 after exposure at 13°C for 30 min, compared to micro-bubbles and the control (distilled water). Therefore, the application of micro-bubbles ozone may be useful method for surface sanitation to control postharvest disease.